Physical and Sensory Characteristic of Arenga-Arrowroot Starch Noodle with Beetroot Extract Addition - Herawati, E.R.N.; Ariani, D.; Miftakhussolikhah, M.; Ningrum, V.A.; Pranoto, Y. (2021)
Arrowroot tuber is plenty available in Indonesia as it has been cultivated widely. Arrowroot flour can be develop in noodle processing combine with arenga starch with ratio 75 : 25. The color characteristic of the noodle was a bright brown-opaque color character, thus, make this noodle is not perceived well by customer. Addition of natural color, i.e. beetroot extract can improve the physical appearance. The purpose of this research was to identify the characteristic (physical and sensory) of the arenga-arrowroot starch noodle with beetroot extract addition. Beetroot extract were added in five different concentrations, namely 20; 30; 40; 50; and 60 w/w. A completely randomized design (CRD) with three repetitions was utilized in the experiment. Color, compression strength, tensile strength, and elongation were all tested physically. Sensory characteristic were analyzed using hedonic test with color, aroma, taste, and overal acceptance parameter. The findings revealed that the inclusion of beetroot extract has an effect on the physical and sensory properties of arenga starch - arrowroot flour noodle. The color brightness, compression test, elongation, and tensile strength of the arenga starch-arrowroot flour noodle would all be reduced if beetroot extract was added. The best sensory characteristic was reach by 20 w/w beetroot extract. Â© Published under licence by IOP Publishing Ltd.